2011
DOI: 10.1371/journal.pone.0016203
|View full text |Cite
|
Sign up to set email alerts
|

An Oral Vaccine Based on U-Omp19 Induces Protection against B. abortus Mucosal Challenge by Inducing an Adaptive IL-17 Immune Response in Mice

Abstract: As Brucella infections occur mainly through mucosal surfaces, the development of mucosal administered vaccines could be radical for the control of brucellosis. In this work we evaluated the potential of Brucella abortus 19 kDa outer membrane protein (U-Omp19) as an edible subunit vaccine against brucellosis. We investigated the protective immune response elicited against oral B. abortus infection after vaccination of mice with leaves from transgenic plants expressing U-Omp19; or with plant-made or E. coli-made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
68
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 66 publications
5
68
0
2
Order By: Relevance
“…80 Similarly, unlipidated outer membrane protein 19 of B. abortus induces a Th17 immune response and confers 1.12 log units of protection against B. abortus 2308 infection in C57BL/6 mice that is independent of TLR4. 81 Our result indicates that rBCSP31 vaccination provides a similar level of protection (1.10 log units of protection) against B. abortus to these single antigens expressed in E. coli. Our results showed that vaccination with rBCSP31 provided a higher level of protection against B. abortus infection in C57BL/ 6micecomparedwithTLR2 2/2 andTLR4 2/2 mice,demonstrating that TLR2 and TLR4 function as important molecules in the rBCSP31-triggered protective immune response.…”
Section: Discussionsupporting
confidence: 51%
“…80 Similarly, unlipidated outer membrane protein 19 of B. abortus induces a Th17 immune response and confers 1.12 log units of protection against B. abortus 2308 infection in C57BL/6 mice that is independent of TLR4. 81 Our result indicates that rBCSP31 vaccination provides a similar level of protection (1.10 log units of protection) against B. abortus to these single antigens expressed in E. coli. Our results showed that vaccination with rBCSP31 provided a higher level of protection against B. abortus infection in C57BL/ 6micecomparedwithTLR2 2/2 andTLR4 2/2 mice,demonstrating that TLR2 and TLR4 function as important molecules in the rBCSP31-triggered protective immune response.…”
Section: Discussionsupporting
confidence: 51%
“…We showed that oral administration of TMC/ Omp31 NPs induces a significant cellular-mixed Th1-Th17 immune response that is in accordance with the observations by Pasquevich et al 36 and Abkar et al 44 that had shown that oral administration of another antigen (plant-expressed Omp19) and TMC/Omp19 elicits a significant cellular-mixed Th1-Th17 immune response. In a study conducted by Abkar et al, oral vaccination with TMC/Omp19 induced immune responses and a high level of protection against systemic infection.…”
supporting
confidence: 92%
“…Currently, licensed human or animal vaccines are generally administered by the parenteral route, but then again, oral vaccines have many advantages compared to systemic injections. 36 As the Brucella bacterium often enters the body via contaminated food and/or water, mucosal immunity can act as a first barrier against the infection before it reaches the bloodstream. 37 Hence, one of the goals of this study was the elicitation of anti-Brucella IgA in mucosal sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subunit recombinant protein vaccines are considered promising vaccines because they are effective, less biohazardous, well-defined, non-infectious and persuade long-actingprotection [5,6].Furthermore, it is essential to ISSN: 2320-5407 Int. J. Adv.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%